PENINGKATAN PEMECAHAN MASALAH MATEMATIS MELALUI MODEL MMP BERBANTUAN MODUL ETNOMATEMATIKA PADA SISWA KELAS IV SDN WONOSEKAR: Penelitian Tindakan Kelas - Siti Hannah Nur Fadzillah; Jayanti Putri Purwaningrum; Savitri Wanabuliandari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2020)
This study aims to describe the application of the MMP (Missouri Mathematic Project) model assisted by the ethnomatematics module to improve students' mathematical problem solving abilities and skills in mathematics, as well as how much the teacher's teaching skills can be improved through the MMP (Missouri Mathematic Project) model assisted by the ethnomatematics module. Data collection techniques used in this study consisted of tests and non-tests. The results of the study there are improvements that include the mathematical problem solving ability of students in the first cycle (70%) increased to (85%) cycle II, then an increase in the teaching skills of the first cycle teacher (78%) increased to (91%) cycle II, and skills students' mathematical problem solving also increased in cycle I (65%) to (95%) cycle II. This proves that the application of MMP (Missouri Mathematic Project) learning model assisted by ethnomatematics modules can improve mathematical problem solving abilities and skills as well as teacher teaching skills.